The Relationship of Teachers’ Work Engagement with Organizational and Personal Variables: A Multiple Mediator Model - Hasan Kavgacı; Temel Çalık (Educational Administration: Theory and Practice, 2021)
The aim of this study is to examine the relationship between primary school teachers’ work engagement and personal and organizational variables. The study was designed as a relational model. Data were gathered from 810 teachers employed in primary education institutions in Ankara in 2012-2013 education year. Utrecht Work Engagement Scale, Leader-Member Exchange Scale, Teacher Autonomy Scale, Brief Resilient Coping Scale, and Teacher Self-Efficacy Scale were used as data collection tools. Findings showed that personal (resilience and self-efficacy) and organizational (leader-member exchange and autonomy) variables were significantly related to work engagement. Personal and organizational variables have a positive and significant effect on work engagement. Moreover, personal variables partially mediating the relationship between organizational variables and work engagement.